Genome Sequencing of Streptomyces atratus SCSIOZH16 and Activation Production of Nocardamine via Metabolic Engineering - Li, Yan; Zhang, Chunyan; Liu, Chengxiong; Ju, Jianhua; Ma, Junying (Frontiers in Microbiology, 2018)
The Actinomycetes are metabolically ﬂexible microorganisms capable of producing a wide range of interesting compounds, including but by no means limited to, siderophores which have high affinity for ferric iron. In this study, we report the complete genome sequence of marine-derived Streptomyces atratus ZH16 and the activation of an embedded siderophore gene cluster via the application of metabolic engineering methods. The S. atratus ZH16 genome reveals that this strain has the potential to produce 26 categories of natural products barring the ilamycins. Our activation studies revealed S. atratus SCSIO ZH16 to be a promising source of the production of nocardamine-type (desferrioxamine) compounds which are important in treating acute iron intoxication and performing ecological remediation. We conclude that metabolic engineering provides a highly effective strategy by which to discover drug-like compounds and new natural products in the genomic era.